DFT And MP2 Based Quantum Mechanical Calculations And A Theoretical Vibrational Spectroscopic Investigation On Roscovitine, A Potential Drug To Treat Cancers - Balcı, Kubilay; Akkaya, Yasemin; Palavan-Ünsal, Narçin; AKYÜZ, SEVİM (Wiley-Blackwell, 111 River St, Hoboken 07030-5774, NJ USA, 2011)
Theoretically possible stable conformers of free roscovitine molecule in its electronic ground state were searched by means of molecular dynamics and energy minimization calculations performed using the MM2 force field. Afterwards, geometry optimization and thermochemistry calculations were carried out at room temperature for each of the found minimum-energy conformers using the MP2 and DFT based electronic structure methods and different Pople-style basis sets. The results obtained from these calculations confirmed that the strong intramolecular hydrogen bonding between the purine-nitrogen and hydroxyl-hydrogen atoms plays an important role on the rigidity of roscovitine molecule and causes a dramatic reduction in the number of the possible stable conformers of this molecule at room temperature. Furthermore, the same calculation results also revealed that two of the found seven stable conformers are considerably more favorable in energy than the others and thus dominate the experimental room-temperature spectra of the molecule. In the light of the theoretical vibrational spectral data obtained for these two conformers, a successful assignment of the fundamental bands observed in the experimental IR and Raman spectra recorded at room temperature for solid roscovitine and for its ethanol solution is given, and the effects of the substitution and intramolecular hydrogen bonding on the fundamental bands associated with purine and phenyl group vibrations are discussed in detail. In the fitting of the calculated harmonic wavenumbers to the corresponding experimental wavenumbers, two different scaling procedures, called 'dual scale factors' and `Scaled Quantum Mechanical Force Field(SQMFF) methodology', were applied independently. Both procedures yielded results generally in good agreement with the experiment; however, the SQM FF methodology proved its superiority over the other. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: roscovitine; IR and Raman spectra; vibrational modes; SQM FF; dual scale factors; cyclin-dependent kinases; density-functional theory; raman-spectra; in-vivo; matrix-isolation; scaling factors; force-fields; cell-cycle; roskovitin; IR ve Raman spektrumları; titreşim modları; çift ölçek faktörleri; yoğunluk fonksiyonel teorisi; Raman spektrumları; matrix-izolasyon; ölçekleme faktörleri; kuvvet alanları; hücre döngüsü